Between frustration and optimism: the development outcome of the Millennium+5 Summit - Markus Loewe; Thomas Fues (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
The Millennium+5 Summit held on the occasion of the United Nations' 60th anniversary did not live up to the great expectations placed in it. But it cannot be said either that the summit failed. Despite a polarization between North and South that grew in intensity in the course of the negotiation process, the 191 UN member countries did, at the last minute, reach agreement on a final document containing a number of noteworthy positions on securing international peace and preventing humanitarian disasters. The document's development-related items – while setting some new accents – are largely in line with the positions reached prior to the summit by the G8 and the European Union. One ground for disappointment may be seen in a number of unbridgeable differences of opinion on UN reform and disarmament. Unlike the world conferences of the 1990s, this years' summit did not signal a new beginning. The steps forward urgently needed in multilateral politics were blocked by deep-seated conflicts of interest between the UN member states. Apparently too few countries have realized that national power politics and the defence of sovereign rights must, under the altered conditions of a growingly interdependent world, necessarily lead to impasse. The achievement of national goals is inextricably bound up with the ability and willingness to tackle global challenges. This is why it is essential for both North and South to acknowledge their common interest in global stability and security, equity and sustainability, and to assume joint responsibility for creating an inclusive global governance architecture and reforming and renewing the UN.
Keywords: 330